«Apocalipsi» (1998): Poetics, Ethics and Reception of Lluïsa Cunillé’s Theatre (Castilla. Estudios de Literatura, 2019)
Taking Apocalipsi (1998) as a paradigmatic play of Lluïsa Cunillé’s theatre, the article explores its compositional strategies of fragmentation, epicisation and rhapsody both to define the “poetics of the subtraction” characteristic of the playwright, and to decipher the correlation between her aesthetics, and the semantics and the reception of her work. The detailed analysis of Apocalipsi’s progressive rupture of the dramatic parameters (fable, action, dialogue and characters) allows for elucidating the crisis of intersubjective relations as the main concern of Cunillé’s drama; it furthermore contributes to identify Rancière’s “emancipated spectator” (2009), who is intellectually active and prepared to assume Levinas’s “ethical responsibility” to the Other (1989), as a model of reception of her dramaturgy.
Keywords: Lluïsa Cunillé; Apocalipsi; dramatic fragmentation; intersubjectivity; Levinasian ethics; theatrical reception